Canvas Model Business Design (BMC) in Karawang Batik Production Business at Bale Batik Taza Karawang - Lina Sukmasari; Dede Jajang Suyaman; Hartelina Hartelina (Universitas Muhammadiyah Jakarta, 2021)
The research objective is to implement the Design strategy to develop the Karawang Batik Business by using the design of the nine elements of the Canvas business model which includes Customer segment, value proposition, channel, customer relationship, revenue stream, key resources, key activities, key partnership, cost structure. This Canvas Model is expected to be able to overcome and provide solutions to problems and obstacles from all activities or activities at Bale Batik Taza Karawang which until now seems to have not been fully implemented so that researchers want to create, map, design, and direct what indicators should be improved to build a business that it can produce maximum production, marketing, and sales. The type of research used is descriptive with a qualitative approach method. The research location was conducted at Bale Batik Taza, KH. Ahmad Dahlan street No.20 at Karawang city. Respondents were carried out purposively by considering the factors of understanding the company's strategy, company conditions, internal conditions, business models, the company's main competitors. alternative Strength–Opportunity strategy as a strategy to use strengths to take advantage of existing opportunities. The conclusion of the research that can be found is that the mapping of the Canvas business model run by Bale Batik Taza Karawang has not been maximally implemented. Some elements that need to be improved are Key partnership, Key Resource, Key Activity, Customer Relationship, Customer segment, Channel, and Cost Structure. While the approach using SWOT analysis should be more maximal in developing its business innovations such as expanding marketing strategies, networking with vendors, and the quality of the various designs and variations of the typical Karawang batik patterns that are packaged according to consumer demand so that they will be satisfied with the results of the pattern designs made. The strategy is carried out using the S–O, S–T, W–T, and W-O to determine how many strategies can be used to build and develop the Karawang Batik Business at Bale Batik Taza Karawang so that it can increase.